DIAGNOSIS AND PROGNOSIS EVALUATION OF SEVERE PNEUMONIA BY LUNG ULTRASOUND SCORE COMBINED WITH SERUM INFLAMMATORY MARKERS. - Fu, Bo; Zhang, Peng; Zhang, JunHua (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Objective: To analyze the significance of lung ultrasound score (LUS) combined with serum inflammatory indexes in different severities of severe pneumonia and and its clinical value on prognosis. Methods: A total of 100 patients with severe pneumonia who were treated in the Gansu Provincial Hospital from June 2017 to June 2021 were selected as the research objects. According to the acute physiology and chronic health (APACHE II) score, they were divided into low-risk group (28 cases) and medium-risk group (39 cases) and high-risk group (33 cases). The general clinical data of the patients (age, gender, smoking history, and underlying diseases) were collected, the lung ultrasound score (LUS) of the patients was measured, and the serum inflammatory indicators (IL-6, IL-10, TNF-α, CRP and NLR) levels; pearson correlation analysis to evaluate the correlation between LUS score, serum inflammatory index levels and disease severity; receiver operating characteristic (ROC) curve analysis to evaluate the prognostic value of the combined diagnosis of LUS score and serum inflammatory index for the severity of severe pneumonia. Results: With the increase of the severity of severe pneumonia, the LUS score and the level of inflammation in the body continued to increase, and LUS combined with serum inflammatory indexes could distinguish the severity of low-risk, medium-risk and high-risk of severe pneumonia, and had high diagnostic value. In addition, the combined diagnosis of LUS and serum inflammatory markers is also closely related to the prognosis of patients with severe pneumonia, which can distinguish the prognosis. Conclusion: LUS combined with serum inflammatory indicators (IL-6, IL-10, TNF-α, CRP and NLR) can differentiate the severity and prognosis of severe pneumonia, which may be a new direction for the diagnosis of severe pneumonia and guide early clinical intervention.